Effects of Vitamin D3 (Cholecalciferol) on Adriamycin-Induced Nephrotoxicity - Dabak, Durrin Ozlem; Kuloglu, Tuncay; Ozercan, Mehmet Resat (Taylor & Francis Ltd, 2009)
Although immune-mediated pathogenesis in adriamycin (ADR)-induced nephropathy has been proposed recently, studies are lacking about the effects of immunmodulators, such as vitamin D, on ADR-induced nephrotoxicity. We hypothesized that vitamin D-3 (cholecalciferol) would be beneficial on ADR-induced nephropathy because of its immunmodulatory properties. Eighteen male Wistar rats were divided into three groups (n = 6): group 1 (control), group 2 (single ADR injection intravenously), and group 3 (similar single ADR injection intravenously + daily oral cholecalciferol for 21 days) were used in the study. A single high dose of ADR resulted in increased urinary protein: creatinine ratio for all three weeks of the experiment in both groups 2 and 3 compared with the controls. Histological examination of the kidney tissue revealed distinct tubular lesions as tubular necrosis, hyaline casts in tubular lumen, tubular degeneration, tubular dilatation, and tubular vacuolization in group 2 compared with group 1. These tubular lesions were significantly reduced in group 3 compared to group 2. The results of this study indicate that cholecalciferol causes satisfactory tubulointerstitial recovery in ADR-induced nephrotoxicity in rats.
Keywords: adriamycin; nephrotoxicity; vitamin D